MALTHUS ON SEX, PROCREATION, AND APPLIED ETHICS - Cremaschi, Sergio (Pensando - Revista de Filosofia, 2017)
I argue that Malthus’s Essay on Population is more a treatise in applied ethics than the first treatise in demography. I argue also that, as an ethical work, it is a highly innovative one. The substitution of procreation for sex as the focus makes for a drastic change in the agenda. What had been basically lacking in the discussion up to Malthus’s time was a consideration of human beings’ own responsibility in the decision of procreating. This makes for a remarkable change also in the approach, namely, the discussion becomes an examination of a well-identified issue, taking cause-effect relationships into account in order to assess possible lines of conduct in the light of some, widely shared and comparatively minimal, value judgements. This is more or less the approach of what is now called applied ethics, at least according to one of its accounts, or perhaps to the account shared by a vast majority of its practitioners. In a sense, both the subject matter, sexuality, was substituted with a more restricted issue, namely reproduction, and the traditional approach, moral doctrine, was substituted with a more modest approach, in Malthus’s own words, the “moral and political science”. Such a drastic transformation brought about a viable framework, for a discussion of ethical issues that were still unforeseen by Malthus, namely those having to do first with the technical feasibility of eugenics programs and secondly with the scientific discovery of genetics as a field of study but also of possible intervention. Malthus’s ethics had obviously enough nothing to say on those unforeseen issues in so far as it was meant to treat just the ‘quantitative’ dimension of procreation, that is, “how many”. Later discussions and controversies will arise around different dimensions, that is, not just ‘how many’ but also ‘how healthy, how strong, how far empowered’. Yet, what Malthus’s lesson can still teach to proponents of opposite views is that the mentioned questions can be construed in such a way as to avoid unending controversy.